2005
DOI: 10.1111/j.1399-6576.2005.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in coagulation‐fibrinolysis marker and neutrophil elastase following the use of tourniquet during total knee arthroplasty and the influence of neutrophil elastase on thromboembolism

Abstract: We suggest that during TKA, the use of tourniquet induces local release of a large amount of NE from neutrophils, inducing the development of DVT and/or PTE and their exacerbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
1
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 31 publications
(35 reference statements)
2
37
1
8
Order By: Relevance
“…31 In addition, intra-articular tranexamic acid injection has the advantage of inducing partial microvascular hemostasis by stopping fibrin clot dissolution in the affected area. 32 Although the current authors were able to show a significant improvement in the postoperative hemoglobin decrease, they were unable to show an improvement in the rate or number of units needed to transfuse. Because no clear parameters were defined in either group for the indications for transfusion, it was likely susceptible to bias.…”
Section: Discussioncontrasting
confidence: 58%
“…31 In addition, intra-articular tranexamic acid injection has the advantage of inducing partial microvascular hemostasis by stopping fibrin clot dissolution in the affected area. 32 Although the current authors were able to show a significant improvement in the postoperative hemoglobin decrease, they were unable to show an improvement in the rate or number of units needed to transfuse. Because no clear parameters were defined in either group for the indications for transfusion, it was likely susceptible to bias.…”
Section: Discussioncontrasting
confidence: 58%
“…Previously we demonstrated that during TKA, the use of a tourniquet increased the NE level 8-fold and suggested that this event may promote the risk of developing PTE, particularly in RA patients [21,37] . On the other hand, the absence of PTE has been associated with a general status of decline in hypercoagulability [26,37] . We attributed this to the so-called 'reperfusion injury', that is to say the release of NE by deflating tourniquet was the most important factor [25,38] .…”
Section: Discussionmentioning
confidence: 89%
“…In one study the levels of blood coagulation-fibrinolysis markers, TAT and D-dimer, in the group with a tourniquet were significantly higher compared with the levels in the group without a tourniquet [24]. And increases in fibrinolytic activity in the systemic circulation following the release of occlusive limb tourniquet have been described by other authors [25][26][27].…”
Section: Discussionmentioning
confidence: 83%